Antimicrobial resistance: capacity and practices among clinical laboratories in Kenya, 2013 - Odhiambo, Fredrick (Pan Afr Med J, 2014)
INTRODUCTION: Antimicrobial resistance is neglected in developing countries; associated with limited surveillance and unregulated use of antimicrobials. Consequently, delayed patient recoveries, deaths and further antimicrobial resistance occur. Recent gastroenteritis outbreak at a children's home associated with multidrug resistant non-typhoidal Salmonella spp, raised concerns about the magnitude of the problem in Kenya, prompting antimicrobial resistance assessment preceding surveillance system establishment. METHODS: Eight public medical laboratories were conveniently selected. Questionnaires were administered to key informants to evaluate capacity, practice and utilization of antimicrobial susceptibility tests. Retrospective review of laboratory records determined antimicrobial resistance to isolates. Antimicrobial resistance was defined as resistance of a microorganism to an antimicrobial agent to which it was previously sensitive and multidrug resistance as non-susceptibility to at least one agent in three or more antimicrobial categories. RESULTS: The laboratories comprised; 2(25%) national, 4(50%) sub-national and 2(25%) district. Overall, antimicrobial susceptibility testing capacity was inadequate in all. Seven (88%) had basic capacity for stool cultures, 3(38%) had capacity for blood culture. Resistance to enteric organisms was observed with the following and other commonly prescribed antimicrobials, ampicillin: 40(91%) Salmonella spp isolates; Tetracycline: 16(84%) Shigella flexineri isolates; cotrimoxazole: 20(100%) Shigella spp isolates, 24(91%) Salmonella spp isolates. Comparable patterns of multidrug resistance were evident with Shigella flexineri and Salmonella typhimurium. Ten (100%) clinicians reported not using laboratory results for patient management, for various reasons.